KORELASIONAL ANTARA MANAJEMEN LINGKUNGAN, SOSIAL-EKONOMI DAN KELEMBAGAAN DENGAN PRODUKSI TAMBAK DI WILAYAH KOTA SEMARANG - Rini Budi Hastuti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2009)
The research is held in Northern Coast of Semarang city. The important role of environmental management, social-economic condition, and institution is determining success of a program of coastal society welfare improvement through the program of intercropping embankment (Wanamina), in the other hand, generally, the role and function are not optimally completed. The experiment is to acknowledge the influencing dominant factors toward wanamina embankment production. The purpose of the research is to acknowledge the correlation between enviromental management, social-economy, and institution. The factor of management, social-economy, and institution either separately or jointly is strongly related in positive way with the embankment production. The strong relationship is shown upon the coefficient correlation, which is management variable (r = 0,638), social-economic variable (r = 0,817), and institutional variable (r = 0,870). Whereas, jointly, those three variables possess strong relationship (r = 0,941, to 1) against the embankment production.